Pigmented Poroma in the Groin Area: A Rare Presentation of an Uncommon Entity - Jeanne M. Dsouza; Mariya B. Muringatheri; Ankur Singh; Priyanka Hemrajani (Indian Dermatology Online Journal, 2025)
Eccrine poroma (EP) is a rare benign adnexal tumour originating from sweat glands, typically found on the palms and soles. Pigmented variants are even rarer and can be easily misdiagnosed as other pigmented tumours. This report presents a unique case of pigmented eccrine poroma in a 60-year-old female. The lesion was located in the groin which is an uncommon site for EP. The patient had a slowly growing, painful nodule. Several differential diagnoses were initially considered. Histological examination confirmed the diagnosis of pigmented eccrine poroma, revealing characteristic features such as small cuboidal cells with basophilic nuclei and melanin deposition. This case underscores the importance of considering pigmented eccrine poroma in the differential diagnosis of solitary pigmented nodules in atypical locations and highlights the role of histopathology and emerging non-invasive diagnostic tools in its accurate identification.